A distributed architecture for efficient Web service discovery. Issue 1 (March 2016) - Baresi, Luciano; Miraz, Matteo; Plebani, Pierluigi
Abstract Although the definition of service-oriented architecture (SOA) included the presence of a service registry from the beginning, the first implementations (e.g., UDDI) did not really succeed mainly because of security and governance issues. This article tackles the problem by introducingDREAM (Distributed Registry by ExAMple): a publish/subscribe-based solution to integrate existing, different registries, along with a match-making approach to ease the publication and retrieval of services.DREAM fosters the interoperability among registry technologies and supports UDDI, ebXML Registry, and other registries. The publish/subscribe paradigm allows service providers to decide the services they want to publish, and requestors to be informed of the services that satisfy their interests. As for the match-making, DREAM supports different ways to evaluate the matching between published and required services. Besides presenting the architecture ofDREAM and the different match-making opportunities, the article also describes the experiments conducted to evaluate proposed solutions.